A Robust Nonlinear Control Strategy for Unsupported Paraplegic Standing Using Functional Electrical Stimulation: Controller Synthesis and Simulation - Ruhbakhsh, Seyedeh Sakineh; Kobravi, Hamid Reza (International Clinical Neuroscience Journal, 2020)
Background: Functional electrical stimulation (FES) is known as a promising technique for movement generation in the paralyzed limbs through electrical stimulation of the muscle nerves. This paper focuses on the FES based control of upright standing in paraplegic patients. In this study a new approach for controlling the upright posture has been proposed. The posture control strategies proposed in the previous works were based on controlling the angular joint position, and none of them were focused on controlling the CoP dynamics directly. Since the CoP is representative of posture balance dynamics, in this study the adopted FES based control strategy was designed to control the CoP dynamics directly. Method: In the proposed strategy, the controller has determined the stimulation intensity of ankle muscles in a manner to restrict the center of pressure (CoP) in a specific zone to guarantee the posture balance during unsupported standing. The proposed approach is based on a new cooperative based combination between two different controllers. Utilizing this strategy, until the CoP is confined within the stable zone, an adaptive controller is active and tries to preserve the posture stability. When the CoP goes out the stable zone, sliding mode control, as a nonlinear control technique presenting remarkable properties of robustness, is activated and tries to back the CoP within the preference zone. In this manner, not only the posture balance can be guaranteed but also the balance dynamics can be similar to the elicited dynamic postural behavior in the normal subjects. Results: Extended evaluations carried out through the simulation studies on a musculoskeletal model. According to the achieved results, the proposed control strategy is not only robust against the external disturbances but also insensitive to the initial postural conditions. Conclusion: The achieved results prove the acceptable performance of the proposed control strategy.